Encyclopedia of Judaism - Karesh, Sara E.; Hurvitz, Mitchell M. (New York : Facts on File, 2006)
Encyclopedia of Judaism explores a tradition that has a 2,000-year recorded history and has been a part of the culture of almost every country and society around the globe. Encapsulating all things Jewish--language, laws, literature, arts, theology, ritual, land, culture, and personalities--this authoritative volume offers readers ba access to Judaism from both a historical and contemporary perspective.
About the Editor -- List of Illustrations -- Preface -- Acknowledgments -- Note on Transliteration -- Introduction: Judaism -- Entries A to Z -- Bibliography -- Index.
Includes bibliographical references (pages 576-582) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Judaism -- Encyclopedias; Judaism -- Encyclopedias; Judaïsme -- Encyclopédies.; RELIGION -- Judaism -- General; Judaism; Judentum; Wörterbuch; Jodendom; encyclopedias; Encyclopedias; Encyclopedias; Encyclopédies.